1991
DOI: 10.1021/bi00239a034
|View full text |Cite
|
Sign up to set email alerts
|

Active site of DNA photolyase: tryptophan-306 is the intrinsic hydrogen atom donor essential for flavin radical photoreduction and DNA repair in vitro

Abstract: DNA photolyases repair cyclobutadipyrimidines (Pyr()Pyr) in DNA by photoinduced electron transfer. The enzyme isolated from Escherichia coli contains methenyltetrahydrofolate (MTHF), which functions as photoantenna, and FADH2, which is the redox-active cofactor. During purification, FADH2 is oxidized to the blue neutral radical form, FADH., which has greatly diminished activity. Previous nanosecond flash photolysis studies [Heelis, P.F., Okamura, T., & Sancar, A. (1990) Biochemistry 29, 5694-5698] indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 39 publications
9
170
0
6
Order By: Relevance
“…We stress that the identity of RP2 in AtCry is not crucial for the interpretation of the magnetic-field effects reported below. In light of previous work (9,10,24,28,29), the Trp radicals are presumed to come from the terminal residue of the Trp-triad, i.e. Trp-324 in AtCry and Trp-306 in EcPL.…”
Section: Resultsmentioning
confidence: 99%
“…We stress that the identity of RP2 in AtCry is not crucial for the interpretation of the magnetic-field effects reported below. In light of previous work (9,10,24,28,29), the Trp radicals are presumed to come from the terminal residue of the Trp-triad, i.e. Trp-324 in AtCry and Trp-306 in EcPL.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli photolyase, the "Trp triad," FADH°←Trp-382←Trp-359←Trp-306 is the predominant photoreduction pathway with Trp-306 being the ultimate electron donor (Fig. 8A) (Li et al 1991;Park et al 1995;Kavakli and Sancar 2004). Interestingly, the residues of this "Trp triad" are conserved in most DNA photolyases and CRYs Lin and Shalitin 2003;Zeugner et al 2005).…”
Section: The "Trp Triad" and Photoreductionmentioning
confidence: 99%
“…Interestingly, the residues of this "Trp triad" are conserved in most DNA photolyases and CRYs Lin and Shalitin 2003;Zeugner et al 2005). It has been unequivocally shown that this pathway has no role in the photocycle of photolyase (Li et al 1991;Kavaklı and Sancar 2004). In contrast, as will be discussed below, some studies have suggested that photoinduced electron 126 ÖZTÜRK ET AL.…”
Section: The "Trp Triad" and Photoreductionmentioning
confidence: 99%
“…1). Earlier biochemical studies (14) as well as X-ray structures (12) identified the conserved tryptophan triad (W382, W359, and W306) as the main electron source for photoreduction, and the recent ultrafast studies (15)(16)(17) of semiquinone FADH ‱ photoreduction revealed the continuing hopping mechanism along the tryptophan triad. The hopping mechanism, consisting of multiple tunneling steps, has been shown to significantly accelerate electron transport in DNA (18) and also recently in proteins (19).…”
mentioning
confidence: 99%